The Oxidative Damage and Inflammation Mechanisms in GERD-Induced Barrett’s Esophagus - Han, Deqiang; Zhang, Chao (Frontiers in Cell and Developmental Biology, 2022)
Barrett’s esophagus is a major complication of gastro-esophageal reflux disease and an important precursor lesion for the development of Barrett’s metaplasia and esophageal adenocarcinoma. However, the cellular and molecular mechanisms of Barrett’s metaplasia remain unclear. Inflammation-associated oxidative DNA damage could contribute to Barrett’s esophagus. It has been demonstrated that poly(ADP-ribose) polymerases (PARPs)-associated with ADP-ribosylation plays an important role in DNA damage and inflammatory response. A previous study indicated that there is inflammatory infiltration and oxidative DNA damage in the lower esophagus due to acid/bile reflux, and gastric acid could induce DNA damage in culture esophageal cells. This review will discuss the mechanisms of Barrett’s metaplasia and adenocarcinoma underlying oxidative DNA damage in gastro-esophageal reflux disease patients based on recent clinical and basic findings.